The Complete Chloroplast Genome Of Castanopsis Fargesii Franch. (Fagaceae) - Xue-Min Ye; Yang-Ping Guo; Xian-Gao Lei; Rong-Xi Sun (Mitochondrial DNA. Part B. Resources, 2019)
Castanopsis fargesii (Fagaceae) is a major dominant tree species in evergreen broad-leaved forests of subtropical China, with significant ecological and economical values. The complete chloroplast genome sequences of C. fargesii was reported based on the Illumina Hiseq 2500 platform. The complete chloroplast genome was 160,601 bp with a typical quadripartite structure, containing a pair of inverted repeated (IR) regions (25,693 bp) that was separated by a large single copy (LSC) region of 90,258 bp, and a small single copy (SSC) region of 18,987 bp. It harbours 123 functional genes, including 78 protein-coding genes, 37 transfer RNA and 8 ribosomal RNA genes. The ML phylogenetic analysis indicated C. fargesii is closely related to Castanopsis hainanensis.